Cks1 Is Required for Tumor Cell Proliferation but Not Sufficient to Induce Hematopoietic Malignancies - Kratzat, Susanne (Public Library of Science, 2012)
The Cks1 component of the SCF(Skp2) complex is necessary for p27(Kip1) ubiquitylation and degradation. Cks1 expression is elevated in various B cell malignancies including Burkitt lymphoma and multiple myeloma. We have previously shown that loss of Cks1 results in elevated p27(Kip1) levels and delayed tumor development in a mouse model of Myc-induced B cell lymphoma. Surprisingly, loss of Skp2 in the same mouse model also resulted in elevated p27(Kip1) levels but exhibited no impact on tumor onset. This raises the possibility that Cks1 could have other oncogenic activities than suppressing p27(Kip1). To challenge this notion we have targeted overexpression of Cks1 to B cells using a conditional retroviral bone marrow transduction-transplantation system. Despite potent ectopic overexpression, Cks1 was unable to promote B cell hyperproliferation or B cell malignancies, indicating that Cks1 is not oncogenic when overexpressed in B cells. Since Skp2 overexpression can drive T-cell tumorigenesis or other cancers we also widened the quest for oncogenic activity of Cks1 by ubiquitously expressing Cks1 in hematopoetic progenitors. At variance with c-Myc overexpression, which caused acute myeloid leukemia, Cks1 overexpression did not induce myeloproliferation or leukemia. Therefore, despite being associated with a poor prognosis in various malignancies, sole Cks1 expression is insufficient to induce lymphoma or a myeloproliferative disease in vivo.